Simultaneous molecular detection of Anaplasma marginale and Theileria annulata in cattle blood samples collected from Pakistan-Afghanistan boarder region. - Sania Jamil; Chien-Chun Chiou; Hira Muqaddas; Hayat Ullah; Muhammad Asif; Sana Rao; Hafsa Hussain; Qandeel Fatima; Nasreen Nasreen; Sadaf Niaz; Karla Dzul-Rosado; Adil Khan; et al. (PLoS ONE, 2023)
Theileria annulata (T. annulata) and Anaplasma marginale (A. marginale) are among the most extensively reported tick borne pathogens and are associated with huge economic losses worldwide. A total of 298 cattle blood samples were screened to report the presence of these two pathogens. The samples were collected from apparently healthy cattle (Achai, n = 155, Jersy, n = 88 and crossbred, n = 55) in Bajaur district of Khyber Pakhtunkhwa (KPK) during June and July of 2022. A total of 31 out of 298 cattle (10.4%) were found infected with T. annulata as PCR amplified a 156 base pair fragment from Tams-1 gene of T. annulata from their blood. While 16/298 animals (5.4%) were found infected with A. marginale as they amplified a 382 base pair fragment specific for msp5 gene of this bacterium. Three animals (1%) were found co infected. Cattle susceptibility to T. annulata infection was significantly higher than A. marginale infection (P < 0.001). Phylogenetic analysis revealed that Pakistani isolates of both detected pathogen clustered together and were closely related isolates from worldwide countries. Prevalence of T. annulata varied significantly among the sampling sites (P = 0.05) while no such association was observed for A. marginale among the tested cattle. Epidemiological data analysis revealed that none of the studied risk factors was found associated either with the prevalence of T. annulata or A. marginale (P > 0.05) among enrolled cattle. In conclusion, our study has revealed a relatively higher prevalence of T. annulata than A. marginale in cattle from the Bajaur district in KPK. This information is important for improving the productivity of the livestock sector, which is one of the main sources of income in the country. It is recommended that this data be taken into account for the development and implementation of effective tick control programs, as well as for the improvement of livestock management practices to prevent and manage TBDs in Pakistan.